Les edicions catalanes del Pierres de Provença: estat de la qüestió. - PASTOR BRIONES, VICENT (Scripta, 2016)
The anonymous novel Pierres de Provença has come to us from a French original written in the mid-fifteenth century through some of the Spanish and Catalan translations carried out since the beginning of the sixteenth century. Despite the little attention that it has received from most historians of literature, the adventures of the knight Pierres and the beautiful Magalona have had readers uninterruptedly up to the nineteenth century. This short chivalric story is one of the few works that make up the catalog of the Catalan prose of the modern period, and therefore it is quite convenient to make a thorough cataloguing of the editions made in order to establish an accurate census that allows to study the work and build up a critical edition. We have been able to establish a list of eleven editions verified by the bibliographers, of which only nine have been preserved. The chronology of most of the editions is, by now, just approximate, except those that have a specified date print on the cover: 1650, 1683 and 1908.